2008
DOI: 10.2319/111907-539.1
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Treatment Combined with Mandibular Distraction Osteogenesis and Changes in Stomatognathic Function

Abstract: We performed an orthodontic treatment combined with mandibular distraction osteogenesis in a 15-year-old patient who wanted a correction of a chin deficiency and a protruding upper lip. The patient had an Angle Class II division 1 malocclusion with mandibular retrusion, a low mandibular plane angle, and scissors bite. First, a quad-helix appliance was applied to the mandibular dentition to correct the scissors bite in the bilateral premolar region. Later, a preadjusted edgewise appliance was applied to the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In humans, masseter muscle EMG activity is higher on the side with the greater occlusal contact during submaximal clenching . In patients with scissors bite, the occlusal contact area was reduced because of a lack of intercuspation of the maxillary and mandibular teeth . It is thought that the loss of occlusal contact area on the scissors‐bite side is related to our results that show a decrease in masseter and temporal activity on the scissors‐bite side during masticatory chewing.…”
Section: Discussionsupporting
confidence: 49%
“…In humans, masseter muscle EMG activity is higher on the side with the greater occlusal contact during submaximal clenching . In patients with scissors bite, the occlusal contact area was reduced because of a lack of intercuspation of the maxillary and mandibular teeth . It is thought that the loss of occlusal contact area on the scissors‐bite side is related to our results that show a decrease in masseter and temporal activity on the scissors‐bite side during masticatory chewing.…”
Section: Discussionsupporting
confidence: 49%
“…The goal of orthodontic treatment is to improve dentofacial aesthetics and function . It has been reported that masticatory function such as masticatory chewing pattern, masticatory muscle activity, maximum occlusal force (MOF) and occlusal contact area (OCA) improved after orthodontic treatment …”
Section: Introductionmentioning
confidence: 99%
“…In a measurement of physical function, HS is used as a convenient and useful measurement method, and collated with lower arm and leg strength . On the other hand, MOF and OCA is associated with maxillofacial morphology, such as high mandibular plane (Mp) angle and long face, and with malocclusion such as open bite, posterior crossbite and scissor bite . However, the relationships between maxillofacial morphology/malocclusion and HS remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Malocclusion has been reported [8][9][10][11][12] to induce predominantly vertical or chopping type chewing and a prolonged cycle duration during chewing. While the chewing pattern of patients with a Class II division 2 malocclusion remains to be established, studies 20,21 have suggested that deep bite malocclusion influences the shape of the chewing cycle and the consistency of chewing cycle kinematics.…”
Section: Class II Division 2 Treatment and Functional Changesmentioning
confidence: 99%
“…Discrepancies in the posterior area have been assigned great importance in decisions regarding tooth extraction. 6,7 Malocclusion has been reported [8][9][10][11][12] to reduce stomatognathic function during mastication. However, the chewing pattern of a patient with a Class II division 2 malocclusion and the changes in stomatognathic function after orthodontic treatment remain unclear.…”
Section: Introductionmentioning
confidence: 99%